Biosynthesis of Silver Nanoparticles Using Seasonal Samples of Sonoran Desert Propolis: Evaluation of Its Antibacterial Activity against Clinical Isolates of Multi-Drug Resistant Bacteria - Pablo Mendez-Pfeiffer; Manuel G. Ballesteros-Monrreal; Jesus Gaona-Ochoa; Josue Juarez; Marisol Gastelum-Cabrera; Beatriz Montaño-Leyva; Margarita Arenas-Hernández; Liliana Caporal-Hernandez; Jesús Ortega-García; Edwin Barrios-Villa; Carlos Velazquez; Dora Valencia (MDPI AG, 2022)
Multi-drug resistant (MDR) bacteria have gained importance as a health problem worldwide, and novel antibacterial agents are needed to combat them. Silver nanoparticles (AgNPs) have been studied as a potent antimicrobial agent, capable of countering MDR bacteria; nevertheless, their conventional synthesis methods can produce cytotoxicity and environmental hazards. Biosynthesis of silver nanoparticles has emerged as an alternative to reduce the cytotoxic and environmental problems derived from their chemical synthesis, using natural products as a reducing and stabilizing agent. Sonoran Desert propolis (SP) is a poplar-type propolis rich in polyphenolic compounds with remarkable biological activities, such as being antioxidant, antiproliferative, and antimicrobial, and is a suitable candidate for synthesis of AgNPs. In this study, we synthesized AgNPs using SP methanolic extract (SP-AgNPs) and evaluated the reduction capacity of their seasonal samples and main chemical constituents. Their cytotoxicity against mammalian cell lines and antibacterial activity against multi-drug resistant bacteria were assessed. Quercetin and galangin showed the best-reduction capacity for synthesizing AgNPs, as well as the seasonal sample from winter (SPw-AgNPs). The SPw-AgNPs had a mean size of around 16.5 ± 5.3 nm, were stable in different culture media, and the presence of propolis constituents was confirmed by FT-IR and HPLC assays. The SPw-AgNPs were non-cytotoxic to ARPE-19 and HeLa cell lines and presented remarkable antibacterial and antibiofilm activity against multi-drug resistant clinical isolates, with E. coli 34 and ATCC 25922 being the most susceptible (MBC = 25 μg/mL), followed by E. coli 2, 29, 37 and PNG (MBC = 50 μg/mL), and finally E. coli 37 and S. aureus ATCC 25923 (MBC = 100 μg/mL). These results demonstrated the efficacy of SP as a reducing and stabilizing agent for synthesis of AgNPs and their capacity as an antibacterial agent.